2013
DOI: 10.1093/molehr/gat095
|View full text |Cite
|
Sign up to set email alerts
|

Human uterine and placental arteries exhibit tissue-specific acute responses to 17 -estradiol and estrogen-receptor-specific agonists

Abstract: The discrete regulation of vascular tone in the human uterine and placental circulations is a key determinant of appropriate uteroplacental blood perfusion and pregnancy success. Humoral factors such as estrogen, which increases in the placenta and maternal circulation throughout human pregnancy, may regulate these vascular beds as studies of animal arteries have shown that 17β-estradiol, or agonists of estrogen receptors (ER), can exert acute vasodilatory actions. The aim of this study was to compare how acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 36 publications
7
47
0
4
Order By: Relevance
“…As has been shown for other agonists, estrogen receptor-selective agonists display a marked anatomic heterogeneity in arteries of female rodents, with some vessels responding negligibly while others show rapid relaxation in response to activation of ERs or GPER (Reslan et al, 2013). A similar heterogeneity has recently been reported to be present in human uterine and placental arteries (Corcoran et al, 2013). The implications of such heterogeneity for vascular protection and susceptibility to disease development have been recently discussed (Barton et al, 2013).…”
Section: New Aspects Of Gper Function In the Cardiovascular Systemsupporting
confidence: 82%
“…As has been shown for other agonists, estrogen receptor-selective agonists display a marked anatomic heterogeneity in arteries of female rodents, with some vessels responding negligibly while others show rapid relaxation in response to activation of ERs or GPER (Reslan et al, 2013). A similar heterogeneity has recently been reported to be present in human uterine and placental arteries (Corcoran et al, 2013). The implications of such heterogeneity for vascular protection and susceptibility to disease development have been recently discussed (Barton et al, 2013).…”
Section: New Aspects Of Gper Function In the Cardiovascular Systemsupporting
confidence: 82%
“…In the rat uterus, GPR30 has been implicated in estrogen-mediated reduction in vascular tone (Tropea et al 2015) but some have suggested this may not be the case in humans (Corcoran et al 2014). Others still have shown a role for GPR30 in regulation of vascular tone in human mammary arteries (Haas et al 2009).…”
Section: Hormonal Control Of Vascular Adaptationmentioning
confidence: 99%
“…While some studies (11,40) have shown intensive immunoreactive signals for both ER␣ and ER␤ in uterine artery tissue sections from latepregnant sheep, another study (69) has suggested that ER␤ may be the main receptor subtype modulated in the uterine artery during gestation. In addition, a study (12) of the uterine circulation in pregnant women has shown that E 2 , PPT, and DPN caused significant relaxation of isolated myometrial arteries with relaxation of E 2 Ͼ DPN Ͼ PPT, whereas G1 did not cause significant relaxation. These observations highlight the importance of further examining ER distribution, activity, and downstream signaling mechanisms in the systemic versus uterine circulation.…”
Section: Er-mediated Inhibition Of Ca 2ϩmentioning
confidence: 99%